The importance of using analytical procedures in the detection of creative accounting practices - هداب, فاطمة فزع; عبد جاسم, ليلى (Journal of Economics and Administrative Sciences, 2020)
The research aims to identify the importance of using analytical procedures in the detection of creative accounting practices. To achieve this goal, (100) questionnaires were prepared and distributed to the auditors in the Federal Financial Supervision Bureau and the authorized auditors' offices and practitioners of the auditing profession in Iraq. For the purpose of testing the research hypothesis and analyzing data, some appropriate statistical methods have been used and the use of the statistical program (SPSS) to analyze the data. The results of the research showed that the analytical procedures and tests applied by the auditor have a role in revealing and limiting creative accounting practices and methods and that auditors use Analytical procedures at all stages of the audit. The most important recommendations reached are the need for auditors to pay attention to the implementation of the auditing process with all elements and components of the financial statements and to use analytical procedures to identify all possible creative accounting practices and methods applied. The need for the Federal Financial Supervision Bureau and the Association of Certified Public Accountants in Iraq to organize training courses for auditors the importance of using analytical procedures in auditing, and to follow developments in international accounting and auditing standards, creative accounting practices, and ways to limit their effects.